Proteoglycan 4 (Lubricin) and regulation of xanthine oxidase in synovial macrophage as a mechanism of controlling synovitis - Khaled A. Elsaid; Ling X. Zhang; Thomas Zhao; Ava Marks; Derek Jenkins; Tannin A. Schmidt; Gregory D. Jay (Arthritis Research & Therapy)
Abstract Background Synovial macrophages (SMs) are important effectors of joint health and disease. A novel Cx3CR1 + TREM2 + SM population expressing the tight junction protein claudin-5, was recently discovered in synovial lining. Ablation of these SMs was associated with onset of arthritis. Proteoglycan 4 (PRG4) is a mucinous glycoprotein that fulfills lubricating and homeostatic roles in the joint. The aim of this work is to study the role of PRG4 in modulating synovitis in the context of SM homeostasis and assess the contribution of xanthine oxidase (XO)-hypoxia inducible factor alpha (HIF-1a) axis to this regulation. Methods We used Prg4 FrtloxP/FrtloxP ;R26 FlpoER/+ , a novel transgenic mouse, where the Prg4 Frt allele normally expresses the PRG4 protein and was designed to flank the first two exons of Prg4 with a flippase recognition target and “LOXP” sites. Inducing flippase activity with tamoxifen (TAM) inactivates the Frt allele and thus creates a conditional knockout state. We studied anti-inflammatory SMs and XO by quantitative immunohistochemistry, isolated RNA and studied immune pathway activations by multiplexed assays and isolated SMs and studied PRG4 signaling dysfunction in relation to glycolytic switching due to pro-inflammatory activation. Prg4 inactivated mice were treated with oral febuxostat, a specific XO inhibitor, and quantification of Cx3CR1 + TREM2 + SMs, XO immunostaining and synovitis assessment were conducted. Results Prg4 inactivation induced Cx3CR1 + TREM2 + SM loss (p < 0.001) and upregulated glycolysis and innate immune pathways in the synovium. In isolated SMs, Xdh (p < 0.01) and Hif1a (p < 0.05) were upregulated. Pro-inflammatory activation of SMs was evident by enhanced glycolytic flux and XO-generated reactive oxygen species (ROS). Febuxostat reduced glycolytic flux (p < 0.001) and HIF-1a levels (p < 0.0001) in SMs. Febuxostat also reduced systemic inflammation (p < 0.001), synovial hyperplasia (p < 0.001) and preserved Cx3CR1 + TREM2 + SMs (p < 0.0001) in synovia of Prg4 inactivated mice. Conclusions PRG4 is a biologically significant modulator of synovial homeostasis via inhibition of XO expression and downstream HIF-1a activation. PRG4 signaling is anti-inflammatory and promotes synovial homeostasis in chronic synovitis, where direct XO inhibition is potentially therapeutic in chronic synovitis.